2020
DOI: 10.1371/journal.ppat.1008772
|View full text |Cite
|
Sign up to set email alerts
|

Babesia bovis Rad51 ortholog influences switching of ves genes but is not essential for segmental gene conversion in antigenic variation

Abstract: The tick-borne apicomplexan parasite, Babesia bovis, a highly persistent bovine pathogen, expresses VESA1 proteins on the infected erythrocyte surface to mediate cytoadhesion. The cytoadhesion ligand, VESA1, which protects the parasite from splenic passage, is itself protected from a host immune response by rapid antigenic variation. B. bovis relies upon segmental gene conversion (SGC) as a major mechanism to vary VESA1 structure. Gene conversion has been considered a form of homologous recombination (HR), a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Importantly, and in contrast to parasites found in circulation in infected animals, in vitro grown parasites develop in the absence of pressure of the immune system, and thus do not need to resort to activating mechanisms involved in antigenic variation, which are required to evade the immune system responses of their natural hosts. These mechanisms are known to require epigenetic modifications, including chromatin re-arrangements ( Mack et al, 2020 ). Altogether, this suggests that Babesia parasites have a great ability to adapt in order to survive in the face of important selective environmental forces ( Lau et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, and in contrast to parasites found in circulation in infected animals, in vitro grown parasites develop in the absence of pressure of the immune system, and thus do not need to resort to activating mechanisms involved in antigenic variation, which are required to evade the immune system responses of their natural hosts. These mechanisms are known to require epigenetic modifications, including chromatin re-arrangements ( Mack et al, 2020 ). Altogether, this suggests that Babesia parasites have a great ability to adapt in order to survive in the face of important selective environmental forces ( Lau et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding led to identification of the ves multigene family encoding VESA1 polypeptides ( Allred et al., 2000 ; Xiao et al., 2010 ), and determination that variation is achieved through a process of segmental gene conversion (SGC) ( Al-Khedery and Allred, 2006 ). During SGC short segments (109 bp on average) of the actively transcribed ves genes are replaced with alternative sequences from silent ves genes in loci scattered about the genome ( Al-Khedery and Allred, 2006 ; Mack et al., 2020 ). The outcome of this back-and-forth between recognition and destruction versus variation and escape is long-term persistence with wide population fluctuations ( Allred et al., 1994 ; Calder et al., 1996 ).…”
Section: Cytoadhesion and Dna Repair Are Related?mentioning
confidence: 99%
“…The ves multigene family is large and scattered over all B. bovis chromosomes ( Al-Khedery and Allred, 2006 ; Brayton et al., 2007 ), yet only one ves locus (comprised of one ves1 α and one ves1 β) is transcriptionally active at a time, the locus of active ves transcription (LAT) ( Al-Khedery and Allred, 2006 ; Żupańska et al., 2009 ; Mack et al., 2020 ). Importantly, transcriptionally active chromatin is more susceptible than silent chromatin to adoption of oxidation-prone higher-order structure, damage, and mutation ( Makova and Hardison, 2015 ).…”
Section: Cytoadhesion and Dna Repair Are Related?mentioning
confidence: 99%
“…To dissect segmental gene conversion through homologous recombination in B. bovis, Mack et al, (2019 2020) disrupted rad51 gene and showed that it is not essential for parasite growth in vitro. However, these parasites lost homologous recombination-dependent gene integration and showed a reduction of in-situ transcriptional switching [9,48]. Recently, a novel multigene family encoding protein with multi-transmembrane domain (mtm) was discovered and overexpressing studies showed that their expression was linked to blasticidin S resistance [26].…”
Section: Genome and Genetic Tools For Babesiamentioning
confidence: 99%
“…can pave the way for finding pan-Babesia drug targets [8]. Several Babesia parasites are being adapted to in vitro culture [9][10][11][12][13][14][15], which facilitate high-throughput compound screens to find novel drugs [16]. However, the molecular targets of the currently available drugs are lagging mainly due to limited genetic tools for these parasites.…”
Section: Introductionmentioning
confidence: 99%